Estrés laboral y síntomas musculoesqueléticos en trabajadores del sector construcción evaluados en un establecimiento de salud ocupacional en la ciudad de Lima – Perú en el año 2017 - Romani Chang, Lenin Ovidio (2020)
Objective: The objective of this research work was to determine the relationship between work stress and musculoskeletal symptoms in workers in the construction sector, evaluated in an occupational health establishment in the city of Lima, year 2017. Materials and methods: It was based on a non-experimental, transverse and correlational design. The population consisted of 561 registers of workers working in the construction sector, who were attended in an occupational health center accredited by the General Directorate of Health, between 01-01-2017 and 31-12- 2017. The entire population studied was taken as a sample. All data was collected from a database that included the results of occupational medical evaluations conducted by physicians certified in occupational medicine, according to current legislation and recorded in the occupational medical record file. The records of the musculoskeletal evaluation record of the aforementioned health facility and the results issued by the ILO-WHO Occupational Stress Scale adapted to Peru. Data processing was done using descriptive statistics, contingency tables and the Ficher's accurate 5% significance test. Results: The global findings indicate a low prevalence of musculoskeletal symptoms at the level of spine, upper and lower limbs, being: 4.5%, 1.4% and 0.9% respectively. Likewise, a low average labor stress level was found in 74% of the sample. Conclusion: There was a significant relationship between thigh skeletal symptoms at spine level and occupational stress (p<0.05). Symptoms at upper and lower limb level were independent of occupational stress level (p>0.05). On the other hand, sociodemographic variables (sex, height, weight, BMI, job profile and seniority) are independent of the type of musculoskeletal symptom (p>0.05). Age was associated with upper limb symptomatology (p <0.05).